NORMAL AND ABNORMAL BLOOD COAGULATION: A SYSTEMATIC REVIEW - Prima , Joses (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The coagulation route is a series of actions that ultimately result in the formation of hemostasis. The intricate process enables quick healing while also helping to avoid bleeding that could otherwise occur on its own. Both the intrinsic and extrinsic routes, which lead to fibrin activation, begin in different places but converge at the same site to produce the same result. The purpose of this procedure is to use a fibrin mesh to help stabilize the ends of the platelets. The mechanism of blood coagulation, which is responsible for maintaining hemostasis, is an intricate process that is carried out by a number of clotting factors. The components I, II, IX, X, XI, and XII are the ones that make up the intrinsic route. Fibrinogen, prothrombin, the Christmas factor, the StuartPrower factor, plasma thromboplastin, and the Hageman factor each have their own names. The variables I, II, VII, and X are the ones that make up the extrinsic route. The factor known as the stable factor is factor VII. The following elements make up the general pathway: I, II, V, VIII, and X. These components, in the form of zymogens, travel through the bloodstream, where they are eventually converted into serine proteases. The process of blood clotting is known as coagulation, and it requires and involves many different components and routes. Disorders that manifest in the organs or components that are essential to the coagulation process can be the root cause of coagulation issues.